2003
DOI: 10.1073/pnas.1833769100
|View full text |Cite
|
Sign up to set email alerts
|

Intra-G 1 arrest in response to UV irradiation in fission yeast

Abstract: G1 is a crucial phase of cell growth because the decision to begin another mitotic cycle is made during this period. Occurrence of DNA damage in G 1 poses a particular challenge, because replication of damaged DNA can be deleterious and because no sister chromatid is present to provide a template for recombinational repair. We therefore have studied the response of Schizosaccharomyces pombe cells to UV irradiation in early G 1 phase. We find that irradiation results in delayed progression through G 1, as manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 57 publications
(53 reference statements)
4
28
0
Order By: Relevance
“…This event occurred at about the same time as Cdc2 became phosphorylated (Fig. 1D), consistent with the preRC data and with the conclusion that this is the time when unirradiated cells enter S phase (9). In cells exposed to UVC, Rum1 disappeared later, 90 min after irradiation, and Cdc2 phosphorylation was detectable only after 120 min ( Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This event occurred at about the same time as Cdc2 became phosphorylated (Fig. 1D), consistent with the preRC data and with the conclusion that this is the time when unirradiated cells enter S phase (9). In cells exposed to UVC, Rum1 disappeared later, 90 min after irradiation, and Cdc2 phosphorylation was detectable only after 120 min ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…UVC Irradiation. A dose of 1,100 J/m 2 of UVC irradiation (254 nm) was given at an incident dose rate of approximately 250 J/m 2 per min in a thin, stirred suspension in EMM medium, as described (9). G 1 -synchronized cells were irradiated immediately after the release from the cdc10 block.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These checkpoints are all dependent on the checkpoint Rad proteins and on one or both of the protein kinases Cds1 and Chk1 that inhibit Cdc2 activity by promoting its phosphorylation. We have recently described a novel checkpoint in S. pombe regulating the G1-S transition (Nilssen et al, 2003;Tvegård et al, 2007), where G1 cells are delayed in Sphase entry after exposure to ultraviolet light (254 nm; UVC). In contrast to the other checkpoints listed above the G1-S checkpoint acts independently of Cds1 and Chk1 and does not lead to Cdc2 phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that ultraviolet (UV) irradiation of fission yeast cells in G1 phase induced a transient delay in S-phase entry (Nilssen et al, 2003). This UV-induced G1-S checkpoint was totally dependent on the Gcn2 kinase and, additionally, UV light led to activation of Gcn2, which in turn resulted in phosphorylation of eIF2a.…”
Section: Introductionmentioning
confidence: 98%